Faktorenanalysen zum Klima Mitteleuropas.: Ein Beitrag zum Problem der Kontinentalität sowie zur Aussagefähigkeit von Faktorenwerten - Kemper, Franz-Josef; Schmiedecken, Wolfgang (ERDKUNDE, 1977)
This contribution follows two aims, which entail a climatological and a methodical problem. Both are connected with the use of factor analytic techniques. The climatological question regarding potential components of continentality or oceanity is tackled with the aid of orthogonal and oblique factor analytic approaches. The methodical problem, on the other hand, consists in the dependence of factor scores on transformations of the initial variables in order to achieve normal distributions. Different authors have been able to show that factor loadings react quite resistently to transformation provided the distribution of variables is not too skewed. In contrast to this, Bahrenberg and Giese have recently pointed out the strong influence of transformations on factor scores. By reanalysing the climatological data these authors had used, it seemed more probable, however, that factor scores,computed by different techniques, are also relatively resistent to transformations of the variables, even if not quite as strongly as factor loadings, and that alterations in the scores correspond to expectations. In a second factor analysis on the climate of Central Europe six factors were extracted and their regional distribution examined, while at the same time the stations were placed more closely and the number of variables was enlarged. It was shown that the scores of the factors “temperature and “precipitation reacted similarly to the corresponding mean annual scores. The scores of the factors “humidity and “cloudiness proved to show a strongly differentiated picture, largely dependent on the relief. The distribution of scores of the factors variation of temperature and “variation of precipitation, which are taken as indicators for a thermic and hygric continentality or oceanity, showed results which were not wholly in accordance with previously held opinions. On the whole, it is possible to summarize this in the following statements: thermic and hygric continentality are not only different in the method of their registration, but they also differ in content in investigations not covering large areas. The be haviour of the two “continentalities is mainly determined through their position on the weather-side or leeward side in smaller areas. The variation of temperature and precipitation often take a contrary course to one another. Only over large areas is it possible to determine a converging degree of continentality with the aid of both methods.